Challenges Faced by Prospective German Language Teachers During Their Teaching Practice: A Case Study of Necmettin Erbakan University - Seval Parlakgüneş Erdoğan (Üniversite Araştırmaları Dergisi)
The development, welfare and peace of a society are directly proportional to the quality of education. In a country with a good education system, the society is also in good condition. One of the essential components of effective and high-quality education is the teacher. The education programs in which teachers are trained are also crucial, as teachers have numerous responsibilities, such as fostering societal development, cultivating skilled human resources, and transferring the culture and values of society to future generations. In these educational programs, the Teaching Practice course holds particular significance. Because this course is the first step of prospective teachers to professional life. In this study, an attempt is made to uncover the potential problems encountered by 21 students who took the Teaching Practice course during the 2022-2023 academic year, as well as any solutions they proposed. This study is analysed through content analysis. The results of the study show that 38% of the 21 pre-service teachers did not experience any problem in the teaching practice, while 62% of them experienced various problems in this process. These problems are such as issues with their supervising teacher, advisor faculty member, self-caused problems and collaboration between the faculty and school. Additionally, teacher candidates offer some solutions to these problems. Notable suggestions include shifting the teaching practice to lower grades instead of the final year, reducing practice hours by 3, holding regular meetings with stakeholders, and conducting awareness-raising meetings for teacher candidates by relevant coordinatorships.